Territorialisation transfrontalière entre Brazzaville et Kinshasa : des ressources marchandes à la frontière ressource - Clémence Auzary (L'Espace Politique)
Relations between Brazzaville and Kinshasa are caught in a permanent paradox of conflicts and cooperation, from the point of view of both states and populations. They have been studied through the lens of the history of the cities’ construction, of the cultural links between the riverbanks, and by the prism of specific cross-border trade channels. This article tackles this paradox with a geographical approach, by studying the spatial differentiation of exchanges between the two cities along the riverbanks. It combines a historical approach to the colonial and post-colonial production of river spaces with a field survey carried out in Brazzaville in 2022 at various river crossing points, and scrutinizes diverse places of crossing at an intra-urban scale, emphasizing the tangible exercise of spatially differentiated power. It combines political geography, which sees territory as shaped by the outcome of the exercise of power and by various power dynamics, with border studies. Drawing initially upon former historical and geographical studies, the article illustrates how the colonial division of territory not only delineated the border but also demarcated power centers from marginal spaces along the riverbanks, where the border is notably porous. It proposes a typology of cross-border spaces in Brazzaville, based on observations and interviews carried out on the banks of the river. Concretely, the exercise of power involves the material infrastructure allowing navigation and the practices of state agents, which are the base of the typology. These differences in the exercise of power are analyzed in terms of spatial distribution of the response to the needs of the State to maintain itself : the assertion of its sovereignty and control of its border and the capacity of the population to meet its basic needs. A “topological” rather than “topographic” approach to power allows understanding the coexistence of central and marginal power structures within the same urban space. The paradox of territorialization arises from the spatially differentiated exercise of state power, creating spaces where the border is more or less tangible, exploitable, and leads to an alternative territorialization surpassing the limit between neighboring sovereignties. The unique spatial configuration of Brazzaville and Kinshasa, two political centers facing each other across the Congo River, allows to understand an exercise of power at the border that is highly contrasting at an intra-urban scale. This contrast aids in understanding the historical paradox of recurring conflicts between public authorities and the sustained cooperation among populations. The interplay of conflict and cooperation articulates differentially depending on the crossing points and the resources exchanged therein. The border between Brazzaville and Kinshasa provides a unique spatial setup to examine conflicts and cooperation in a post-colonial context, focusing on traded goods as resources that turn the border itself into a spatial resource.